Determinants of Entrepreneurial Intentions: Evidence from Undergraduate Students - Ika Nurul Qamari; Siti Aulia Azizah; Dea Farahdiba (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to investigate the determinants of entrepreneurial intentions among undergraduate students. Design/Methods/Approach: The data was collected through a questionnaire survey from 210 undergraduate students who have obtained entrepreneurial subjects based on the purposive sampling technique. The validity and reliability test results prove that all variable indicators met the requirements for the research instrument. The analysis was conducted using multiple linear regression analysis through IBM SPSS 22 software. Findings: The results show that self-efficacy, motivation, risk-taking tendency, entrepreneurial education, and advancement in information technology accelerate students' entrepreneurial intention. Originality: This study explores the theory of reasoned action by using entrepreneurial intentions as the dependent variable. Practical/Policy implication (optional): This study demonstrates that entrepreneurial education and student motivation are significant predictors of entrepreneurial intentions. Therefore, institutions must develop courses emphasizing soft and hard abilities to encourage entrepreneurial intentions. In addition, risk-taking leads to entrepreneurial aspirations through real-world experiences, which should be incorporated into the curriculum for entrepreneurship education.